Friendly Encounters with Literary Animals - László, Borbála (Hungarian Journal of English and American Studies, 2021)
Book review:McHugh, Susan, et al., eds. The Palgrave Handbook of Animals and Literature. Cham, Switzerland: Palgrave Macmillan, 2021. 636 pages. ISBN 978-3-030-39772-2. E-book. €117.69.